2018
DOI: 10.1016/j.cmet.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Inhibition Lowers Plasma Triglyceride-Rich Lipoproteins by Stabilizing the LDL Receptor

Abstract: Excess plasma triglycerides (TGs) are a key component of obesity-induced metabolic syndrome. We have shown that γ-secretase inhibitor (GSI) treatment improves glucose tolerance due to inhibition of hepatic Notch signaling but found additional Notch-independent reduction of plasma TG-rich lipoproteins (TRLs) in GSI-treated, as well as hepatocyte-specific, γ-secretase knockout (L-Ncst) mice, which suggested a primary effect on hepatocyte TRL uptake. Indeed, we found increased VLDL and LDL particle uptake in L-Nc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…Other scholars found that LDLR‐deficient mice had increased secretion of VLDL and TG in the livers. The degradation of LDLR reduced the absorption of TG‐rich VLDL/LDL particles, 28–31 which agrees with our results relating the low expression of LDLR with the elevated secretion of VLDL. The LDLR mRNA level might affect the protein–water stability as a result of post‐translational modification of LDLR protein 32 .…”
Section: Discussionsupporting
confidence: 91%
“…Other scholars found that LDLR‐deficient mice had increased secretion of VLDL and TG in the livers. The degradation of LDLR reduced the absorption of TG‐rich VLDL/LDL particles, 28–31 which agrees with our results relating the low expression of LDLR with the elevated secretion of VLDL. The LDLR mRNA level might affect the protein–water stability as a result of post‐translational modification of LDLR protein 32 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, LDLR is subject to targeted proteolytic cleavage. For example, LDLR was reported recently to undergo γ-secretase-mediated cleavage which in turn induces LDLR lysosomal degradation 10 and the action of an unidentified protease cleaving LDLR within its LA repeats produced a 120 kDa C-terminal fragment (CTF) 11,12 . Further understanding of these proteolytic mechanisms and the role they play could provide additional therapeutic targets for the treatment of hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Next, to ensure reproducibility of these results, we ablated hepatocyte Nicastrin (25), the γ-secretase targeting subunit necessary for ligand-dependent Notch activation ( L-Ncst mice) (26). Similar to L-DNMAM mice, NASH diet–fed L-Ncst mice showed normal body weight and adiposity (fig.…”
Section: Resultsmentioning
confidence: 99%